Penyuluhan E-Commerce sebagai Peluang Ekonomi Karang Taruna Desa Sukmajaya Kabupaten Bogor - Hesti Rosdiana; Shanti Darmastuti; Andi Kurniawan (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2022)
In today's economic development, knowledge and information are developing into one of the main production factors that require technological improvement and innovation to create sustainable economic development. One of its forms is the presence of e-commerce as a means that can help economic activities run more easily and quickly. The improvement of information and technology in supporting e-commerce activities is important to be followed by the community today. In this regard, community service is focused on educating the understanding of e-commerce to increase the economic opportunity of Karang Taruna Sukmajaya Village. This activity was carried out based on the results of discussions with the management of Karang Taruna Sukmajaya Village who wanted to find out more about the economic opportunities of e-commerce. want to find out more about the economic opportunities of e-commerce. In addition, some karang Taruna administrators also have businesses such as in the field of workshops and fisheries, it's just that the marketing method is not based on digital technology. Through this activity, it is hoped that digital literacy related to e-commerce can be a provision in taking advantage of existing economic opportunities. In this case, at least the businesses that have been carried out by the Karang Taruna management can use digital technology to promote their business more broadly. The method used in this service is by providing counseling to the Sukmajaya Village Cadet Reef. The result of this activity is the increasing knowledge and understanding of partners about e-commerce as one of the applications in building the economy of its citizens.